1996
DOI: 10.1046/j.1471-4159.1996.67041726.x
|View full text |Cite
|
Sign up to set email alerts
|

Partitioning of CO2 Production Between Glucose and Lactate in Excised Sympathetic Ganglia, with Implications for Brain

Abstract: Chains of lumbar sympathetic ganglia from 15‐day‐old chicken embryos were incubated for 4 h at 36°C in a bicarbonate‐buffered salt solution equilibrated with 5% CO2‐95% O2. Glucose (1–10 mM), lactate (1–10 mM), [U‐14C]glucose, [1‐14C]glucose, [6‐14C]glucose, and [U‐14C]lactate were added as needed. 14CO2 output was measured continuously by counting the radioactivity in gas that had passed through the incubation chamber. Lactate reduced the output of CO2 from [U‐14C]glucose, and glucose reduced that from [U‐14C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(38 citation statements)
references
References 16 publications
4
34
0
Order By: Relevance
“…Thus, on this basis, it can be argued that lactate might represent a better oxidative substrate than glucose for neurons, at least in vitro. This conclusion is consistent with numerous other studies performed by measuring CO 2 production on synaptic terminals (McKenna et al, 1993(McKenna et al, , 1994(McKenna et al, , 1998, excised sympathetic ganglia (Larrabee, 1996), brain slices (Fernandez and Medina, 1986;Ide et al, 1969), and cultured neurons (McKenna et al, 2001;Tabernero et al, 1996;Vicario et al, 1991), all of which have shown preferential oxidation of lactate over glucose.…”
Section: Discussionsupporting
confidence: 92%
“…Thus, on this basis, it can be argued that lactate might represent a better oxidative substrate than glucose for neurons, at least in vitro. This conclusion is consistent with numerous other studies performed by measuring CO 2 production on synaptic terminals (McKenna et al, 1993(McKenna et al, , 1994(McKenna et al, , 1998, excised sympathetic ganglia (Larrabee, 1996), brain slices (Fernandez and Medina, 1986;Ide et al, 1969), and cultured neurons (McKenna et al, 2001;Tabernero et al, 1996;Vicario et al, 1991), all of which have shown preferential oxidation of lactate over glucose.…”
Section: Discussionsupporting
confidence: 92%
“…The use of lactate as an energy substrate by the frog DRG also concords with observations from studies of mammals and non-mammals. Previous studies showed a preferential use for lactate in avian, mammalian and human neuronal oxidative metabolism (Larrabee, 1980(Larrabee, , 1996BouzierSore et al, 2003BouzierSore et al, , 2006Pellerin and Magistretti, 2012).…”
Section: Discussionmentioning
confidence: 98%
“…The tissues were incubated with 0.15 µCi of 14 C-2-DG plus 10 mM lactate for 60 min under the same conditions initially described. This value was chosen for lactate because it was used in other studies with the ganglion (Larrabee, 1980(Larrabee, , 1996.…”
Section: Glucose Uptakementioning
confidence: 99%
“…Lactate can be used as an oxidative substrate in brain slices (Ide et al, 1969;Fernandez and Medina, 1986), cultured telencephalic neurons (Tabernero et al, 1996;McKenna et al, 2001), aggregated neuronal cultures (Honegger et al, 2002), sympathetic ganglia (Larrabee, 1996), and synaptic terminals (McKenna et al, 1993) and can be preferred to glucose (Bouzier-Sore et al, 2003;Itoh et al, 2003;Smith et al, 2003). In addition, metabolic demands increase neuronal ability to use lactate (Schurr et al, 1999).…”
Section: Discussionmentioning
confidence: 99%